Additions to earthworms (Annelida, Crassiclitellata) from Aragua and Miranda states, Venezuela - Hernández-García, Luis Manuel; Sousa, Sandriel Costa; Pereira, Natália Jovita; Rousseau, Guillaume Xavier; Ferreira, Carmen (Zootaxa, 2023)
Two new species of the earthworm genus Pontoscolex found in San Casimiro County, northern Venezuela are described. Because of some morphological variability, and to improve the previous description, we redescribe Onychochaeta windlei and Rhinodrilus fuenzalidae collected at La Cortada settlement, Miranda state. Pontoscolex (Mesoscolex) juanae sp. n. and Pontoscolex (Nulloscolex) hugoi subgen. n., sp. n have three pairs of tiny calciferous glands in 7th to 9th segments, with a simple tubular structure similar to that of the genus Onychochaeta; however, testes and funnels are enclosed in sacs in the 11th segment similar to the Pontoscolex. We also report the occurrences of Pontoscolex (Pontoscolex) corethrurus Müller, 1857, Metaphire houlleti (Perrier, 1872), Perionyx excavatus Perrier, 1872, Dichogaster bolaui (Michaelsen, 1891), and Eisenia fetida (Savigny, 1826).